Female Sexual Dysfunction: A Case Study of Disease Mongering and Activist Resistance - Tiefer, Leonore (PLoS Medicine, 2006)
"Tiefer highlights key steps in the ""creation"" of a new diagnosis, female sexual dysfunction, and of the campaign to challenge its reductionist approach to women's sexual problems. "
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; corps; cours; discipline; discours dominant; inégalités; patriarcat; postmodernisme; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

Gender Equality in the New Millennium: Goal or Gimmick? - ANTROBUS, PEGGY (Caribbean Quarterly, 2006)
At the Millennium Summit in September 2000 the largest gathering of world leaders adopted the UN Millennium Declaration, committing their nations to a new global partnership to reduce extreme poverty and setting out a series of time-bound targets, all with a deadline of 2015, that have become known as the Millennium Development Goals (MDGs). The Millenium Development Goals are now part of an international development framework which many countries in the Caribbean have signed on to. This paper addresses the question of how the Millenium Development Goals can be made to work to promote gender equality and empowerment in the Caribbean Community (CARICOM) region. The analysis here will not be limited to "gender equality and women's empowerment (MDG Goal 3). It will also highlight the gender dimensions of some of the other MDGs that closely related to women's equality and empowerment - as a means and as an outcome. Finally, the analysis and suggestions in relation to strategies "to ensure that gender inequalities are identified and addressed in the MDG monitoring process and in national policy responses from governments" will focus on Caribbean realities. Suggestions are made by drawing on the findings and insights on the linkages between global trends, development strategies (including the macroeconomic policy framework of structural adjustment) and their impact on poor women, and the ways in which we might now approach activist interventions toward the goal of gender equality and women's empowerment.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; caraïbes; cours; discipline; féminisme des caraïbes; féminismes noirs; histoire et politique; pol4022; premier cycle; pédagogie; périodes historiques; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences de l'éducation; thématiques

Governing women's morality: a study of Islamic veiling in Canada - Atasoy, Y. (EUROPEAN JOURNAL OF CULTURAL STUDIES, 2006)
The veiling of Muslim women is subject to strongly contested ideas about whether the veil is a symbol of women's subordination to an oppressive tradition or a means of emancipation from that tradition. This article suggests that women's own personal reasons for veiling must be analysed. Data collected from published documents from Muslim organizations allows for demonstration that the veil is configured as central to an Islamic moral code of female modesty. A further analysis of findings from interviews conducted with veiled Muslim women in Winnipeg shows the nuanced ways in which women enact this code.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; canada; corps; cours; discipline; féminisme islamique; histoire et politique; identité; manitoba; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sociologie; thématiques; winnipeg

Les conceptions de l’identité sexuelle, le postmodernisme et les textes littéraires - Boisclair, Isabelle; Saint-Martin, Lori (Recherches féministes, 2006)
Le présent article trace d’abord un bref portrait de trois conceptions dominantes de l’identité sexuelle : le modèle patriarcal, le modèle féministe et le modèle postmoderne. Puis, après avoir présenté plus longuement le dernier, il analyse deux romans relayant cette conception postmoderne de l’identité de sexe/genre, l’un écrit par un homme (Self, de Yann Martel, paru en 1996), et l’autre par une femme (Ce qu’il en reste, de Julie Hivon, paru en 1999). Dans ces deux romans, qui revêtent de ce fait une importante dimension politique, les identités figées sont mises à mal tant discursivement que formellement - par la déconstruction des signes du passé et la mise en place de dispositifs énonciatifs confondant hommes et femmes, par exemple. Ils participent ainsi à une conception culturaliste de l’identité sexuelle, selon laquelle le genre est une performance.,This article begins by briefly introducing three major frameworks for conceptualizing gender identity : a patriarchal model, a feminist model and a postmodern model. After exploring the third in greater depth, it offers a reading of two novels of postmodern gender identity, one by a male author (Self by Yann Martel, 1996), one by a female author (Ce qu’il en reste by Julie Hivon, 1999). Both novels, which are therefore strongly political, challenge the concept of predetermined gender identity on the levels both of discourse and of form, by deconstructing older concepts and by blurring gender lines. They are therefore grounded in a view of gender identity as cultural construction and performance.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; cours; discipline; fem1000; premier cycle; périodes historiques; queer; québec; ressource en ligne; régions géographiques; études littéraires

L'écho du féminisme dans les chansons de Jean-Pierre Ferland et de Jim Corcoran - Dubois, Vicky (Université de Montréal, 2006)
Notre étude se penche sur les réactions de deux chanteurs québécois face au mouvement des femmes. Aussi, nous étudions les transformations discursives qu’a subies la chanson québécoise masculine en recherchant les traces du discours féministe dans les paroles des chansons des années soixante-dix à aujourd’hui. Deux figures marquantes de la chanson québécoise, faisant l’objet d’un chapitre chacun, sont analysées Jean-Pierre ferland et Jim Corcoran. À l’aide de l’analyse de discours telle que développée par Marc Angenot et des études comparatistes musico-littéraires proposées par Steven Paul Scher et qui rendent justice à la particularité de la chanson constituée d’un texte, d’une musique et d’une interprétation, nous cherchons à comprendre l’interaction entre la société et la chanson. L’écho du féminisme est audible dans les chansons des auteurs-compositeurs-interprètes et se manifeste, chez Ferland, par son incompréhension des désirs de cette femme métamorphosée par les revendications féministes et, chez Corcoran, par sa volonté de rejoindre la femme émancipée en relançant le dialogue. Ces différences quant à la perception de la femme et de la féminité s’expliquent en grande partie par un effet générationnel. Appartenant à des générations d’hommes qui ont vécu l’essor du féminisme pour l’un et l’apogée du féminisme pour l’autre, les deux chanteurs réagissent différemment au débat sur la différence des sexes et au mouvement des femmes.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; arts; canada; chanson; discipline; masculinité; mémoires/thèses; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques; études littéraires

S’approprier son corps et sa santé. Entretien avec Rina Nissim - Fussinger, Catherine; Rey, Séverine; Vuille, Marilène (Nouvelles Questions Feministes, 2006)
Parmi les personnes qui ont réellement fait avancer les choses et apporté des changements dans la vie de beaucoup de femmes, il y a Rina Nissim qui a oeuvré depuis son engagement au sein du MLF de Genève au début des années 1970 pour que les femmes se réapproprient leur corps et leur santé. Ce numéro de « Nouvelles Questions féministes » sur la santé consacre une bonne partie de ses pages à une discussion avec Rina Nissim. Cette militante du groupe « avortement » et self-help » du MLF genevois raconte comment elle est passée de l'école d'infirmière à une vie de militantisme et de voyages, avec la naturopathie pour bagage. Publiant des ouvrages sur la santé des femmes ayant eu un succès important tel que « Mamamélis », cette pionnière en Suisse ouvre le « dispensaire des femmes »fonctionnant sur un mode autogéré, suite à un voyage aux États-Unis, avec d'autres femmes infirmières psychologues et médecins. Les femmes vont alors trouver une alternative aux rapports de pouvoirs classiques des relations médecin-patient et aux médicaments traditionnels, dans un mouvement de prise de conscience et d'action sur leur propre corps. L'engagement international de Rina, en Amérique Central et en Inde principalement où elle s'installe cinq ans et coordonne différents projets, aura permis a de nombreuses femmes de se découvrir elles-mêmes et les autres, de se débarrasser de la honte et se rendre compte que la maladie est souvent liée à un positionnement social.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique centrale; amérique du nord; amériques; approches et analyses; corps; cours; discipline; discours dominant; europe; france; inde; justice reproductive; premier cycle; périodes historiques; racisme; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; suisse; systèmes d'oppressions; thématiques; travail; états-unis

Anti-Essentialism and Intersectionality - Grillo, Tina (Theorizing feminisms a reader, 2006)
'What is oppression ?' 'What should be done about it ?' Organized around these questions, Theorizing feminisms : a reader provides an overview of theoritical feminist writing about the quest for gender justice. Incorporating both classic and cutting-edge material, the reader takes into account the full diversity of women, highlighting the effects of race, ethnicity, nationality, class, sexuality, and religion on women's experience. Theorizing feminisms is organized into four sections and includes fifty-four essays. The first section introduces several basic concepts commonly employed when thinking about sexism - oppression, social construction, essentialism, intersectionality, gender, race, and class - and also raises questions about the perspective and legitimacy of the theorist. The second section surveys three approaches that attempt to characterize in a general way the source of injustice toward women : humanist feminism ('the sameness approach'), gynocentric feminism ('the difference approach'), and dominance feminism. Offering an alternate perspective, the third section introduces two 'localizing' approaches, grounded in postmodernism and identity politics, respectively. Skeptical of theories that attempt to analyze social phenomena across history and culture, authors in this section challenge, rather than answer, the text's organizing questions. The final section explores the relationship of feminism theory to three liberatory projects - postcolonialism, neo-materialism, and queer theory - that do not characterize themselves as feminist, yet take gender as a significant category of analysis. Each section opens with an introduction and each essay is followed by helpful study questions. the majority of the essays are presented in their entirety. Theorizing feminisms underscores the strong connection between feminist theory and practice by including essays that illustrate important political inspirations or applications of each theoritical approach. It also presents versions of the same approach from various points in history, revealing feminist theory to be dynamic and evolving, rather than static. Ideal for interdisciplinary courses in feminist theory, this volume will also serve as an invaluable reference for current and future generations of theorists."
Keywords: 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; cours; discipline; essentialisme; intersectionnalité; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; thématiques; théorie féministe

Femmes et militantisme - Institut de recherches et d'études féministes (FéminÉtudes, 2006)
Cette publication de 2006 interroge la place et l’importance du militantisme au féminin. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Keywords: 2000 à aujourd'hui; 2000-2009; altermondialisme; amériques; approches et analyses; femmes*; féminétudes; genre; identité sexuelle; identités LGBTQIA2+; inégalités; militance; pratiques féministes; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques

In the days of our grandmothers: a reader in Aboriginal women's history in Canada - Kelm, Mary-Ellen; Townsend, Lorna (University of Toronto Press, 2006)
From Ellen Gabriel to Tantoo Cardinal, many of the faces of Aboriginal people in the media today are women. In the Days of Our Grandmothers is a collection of essays detailing how Aboriginal women have found their voice in Canadian society over the past three centuries. Collected in one volume for the first time, these essays critically situate Aboriginal women in the fur trade, missions, labour and the economy, the law, sexuality, and the politics of representation. (Midwest).
Keywords: 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; commerce; commerce de peaux; cours; discipline; droit; droits des femmes*; droits des femmes* autochtones; famille; féminisme autochtone; histoire; histoire et politique; pol4105; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sexualité; thématiques; travail

Médicalisation de la ménopause, mouvements pour la santé des femmes et controverses sur les thérapies hormonales - Löwy, Ilana; Gaudillière, Jean-Paul (Nouvelles Questions Feministes, 2006)
Le traitement hormonal de la ménopause, présenté entre 1970 et 2000 par la majorité des experts comme capable d’accroître le bien-être des femmes mais aussi de prévenir des nombreuses pathologies liées au vieillissement féminin, a été déclaré en 2002 inutile et dangereux suivant un essai clinique nord américain, Women’s Health Initiative (WHI). En voie de conséquence, les prescriptions de ce traitement ont chuté dramatiquement entre 2002 et 2005. Cet article retrace les origines féministes de WHI, puis suit les conséquences de la publication de ses résultats aux États-Unis, en France et en Allemagne. En conclusion, il revient sur les tensions entre les rôles des femmes comme utilisatrices des hormones, comme expertes et comme militantes des mouvements pour la santé des femmes.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; allemagne; amérique du nord; amériques; approches et analyses; corps; corps des femmes; cours; discipline; discours dominant; europe; france; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

Travail du sexe : tout ce que vous avez toujours voulu savoir, mais n'avez jamais osé demander - Mensah, Maria Nengeh; Lee, Cynthia (Service aux collectivités de l'UQAM/Stella, 2006)
Keywords: 2000 à aujourd'hui; 2000-2009; SAC; amériques; approches et analyses; femmes*; périodes historiques; québec; rapport; rapports sociaux de sexe; régions géographiques; thématiques; travail; travail du sexe; violences

Arab American Femininities: Beyond Arab Virgin/ American(ized) Whore - Naber, Nadine (Feminist Studies, 2006)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; anthropologie culturelle; approches et analyses; arabes-américaines; cours; discipline; discours dominant; femmes* arabes; féminisme islamique; histoire et politique; identités culturelles; intersectionnalité; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; système colonial; systèmes d'oppressions; thématiques; états-unis

Prostitution et immigration des femmes latino-américaines en Espagne - Oso Casas, Laura (Cahiers du Genre, 2006)
L’objectif de cet article est de montrer qu’une bonne partie des femmes latino-américaines, contrairement à l’image souvent mise en avant de la femme objet de trafic, ont pris la décision de migrer en étant conscientes de l’activité qu’elles allaient pratiquer en Espagne. Cependant, bien qu’elles puissent opter volontairement pour le « travail » sexuel, devenant les principales pourvoyeuses économiques des foyers transnationaux (actrices de la migration, actrices économiques et du développement), elles sont prises dans plusieurs circuits qui contribuent à la reproduction des inégalités sociales. Ces circuits sont sous-tendus par l’articulation de plusieurs facteurs : la circulation des personnes, la mobilité des prostituées, la pression du foyer transnational, l’irrégularité juridique, ainsi que l’inégalité de genre.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique centrale; amérique du sud; amériques; approches et analyses; cours; discipline; espagne; europe; immigration; inégalités; migration; postmodernisme; premier cycle; prostitution; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc1061; sociologie; système colonial; systèmes d'oppressions; thématiques; travail

Le sentiment d’insécurité dans les lieux publics urbains et l’évaluation personnelle du risque chez des travailleuses de la santé - Paquin, Sophie (Nouvelles pratiques sociales, 2006)
Le sentiment d’insécurité en milieu urbain est une crainte multiforme basée sur la criminalité, les incivilités et les actes d’intimidation et de violence dans les espaces publics. Le sentiment d’insécurité dans un lieu public est déterminé par une évaluation personnelle du risque. Ce processus d’évaluation permet aux personnes, à la suite d’un indice d’alerte, d’analyser l’environnement global d’un espace public urbain. Cette évaluation personnelle du risque s’effectue grâce à un patron d’organisation de l’information sur l’environnement externe composé de trois pôles : les générateurs microsociaux de l’insécurité, la disponibilité de l’aide et la présence de témoins ; les caractéristiques du milieu bâti ; auxquelles s’ajoutent les variables personnelles de même que le contexte macrosociologique. L’évaluation personnelle du risque permet de reconnaître les facteurs de risque, mais aussi les facteurs de protection dans l’environnement physique et social, comme l’aide disponible, et de les mobiliser pour rétablir la sécurité.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; design; discipline; environnement; milieu urbain; projet charge mentale; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques; urbanisme; violences

Voix alternatives et féministes dans le champ de la santé mentale au Québec - Poirel, Marie-Laurence; Lacharité, Berthe; Rousseau, Ginette (Nouvelles Questions Feministes, 2006)
Au Québec, dans le champ de la santé mentale, l’émergence et la consolidation de discours critiques et de pratiques alternatives aux approches d’intervention dominantes, de plus en plus biomédicales, se sont pour l’essentiel effectuées à l’extérieur du système public de santé et de services sociaux. Ce que l’on appelle ici le Mouvement d’action communautaire autonome a représenté un terreau très fertile pour le déploiement de ces voix et voies alternatives en santé mentale. Cet article s’intéresse plus particulièrement à la contribution de deux catégories d’organismes du Mouvement : les Ressources alternatives en santé mentale et les Centres de femmes, dont l’insertion dans le champ de la santé mentale se situe plus en amont. Par leurs efforts convergents mais aussi par leurs apports différents, ces organismes, qu’ils se disent féministes ou alternatifs, ont significativement contribué au développement d’approches d’intervention sensibles à la complexité de la souffrance psychique dans ses diverses expressions et à l’inscription sociale et sexuée de celles-ci. Représentant des espaces d’appartenance, de parole et d’action, et, souvent, un important levier de transformation personnelle pour les personnes qui les fréquentent, les Ressources alternatives en santé mentale et les Centres de femmes partagent plus largement une culture de transformation sociale.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; inégalités; premier cycle; psychiatrie; périodes historiques; québec; régions géographiques; santé; santé mentale; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques

The Politics of Protection: Body Image, Social Pressures, and the Misrepresentation of Young Black Women - Poran, Maya A. (Sex Roles : A Journal of Research, 2006)
As part of a larger multi-method study, 15 Black women college students participated in focus group discussions on the body. Contrary to popular theories that propose that Black women are protected by a “Black Culture” that buffers them from negative effects of body representations—thereby leaving them with higher body esteem—the themes that emerged in the focus group discussions indicate that young Black women are indeed feeling (1) pressures to be thin, (2) pressures from the preferences of men of diverse ethnicities, (3) competition with other Black women in the realms of beauty, and (4) a strong sense of being misrepresented by media images of thin Black women. These results not only indicate that body image issues are of real pressing concern to young Black women, but that psychological research methodologies may be adding to the misrepresentation of young Black women and their struggles. Qualitative methods must be utilized in order to hear more clearly the voices of Women of Color.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; image corporelle; intersectionnalité; new york; premier cycle; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; états-unis

Grossesse hors mariage dans les familles haïtiennes - Raphaël, Frantz (Santé mentale au Québec, 2006)
Des grossesses précoces chez des jeunes adolescentes haïtiennes de Montréal entraînent des situations de crise qui touchent plusieurs familles, en plus d’interpeller et d’impliquer des intervenants de diverses disciplines. Le sujet, abordé dans un contexte transculturel, fait référence au biculturalisme haïtien, tant en Haïti qu’en terre étrangère. Dans cet article, l’auteur aborde plus particulièrement la situation des Haïtiens dans le contexte québécois. L’analyse de l’attitude des parents des deux groupes culturels, occidentalisé et créole, constitue une lumière médiatrice dans les relations d’aide ou d’intervention psychothérapeutique. Dans la communauté haïtienne, les problèmes d’identité culturelle d’une part, et, le manque d’affiliation à la famille, d’autre part, sont à la base des conflits entre parents et enfants. L’auteur conclut avec des propositions dans le but d’améliorer l’efficacité des interventions avec ces familles dans leur processus d’adaptation migratoire.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; conflit familial; cours; discipline; grossesse hors mariage; haïti; justice sociale; maternité; montréal; premier cycle; psychologie; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexualité; thématiques

Le féminisme, ça clique - Relais-femmes (Service aux collectivités de l'UQAM/Formation à distance à l'intention des groupes de femmes, 2006)
Keywords: 2000 à aujourd'hui; 2000-2009; SAC; amériques; droits des femmes*; formations; histoire du féminisme; périodes historiques; québec; recherche en milieux de pratique; recherche partenariale; ressource en ligne; régions géographiques; thématiques; éducation des femmes*

Global Recognition of Human Rights for Lesbian, Gay, Bisexual, and Transgender People - Suzanne M. Marks (Health and Human Rights, 2006)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; corps; cours; discipline; féminisme décolonial; hétérosexisme; identités LGBTQIA2+; justice sociale; pol4022; premier cycle; périodes historiques; queer; régions géographiques; science politique; systèmes d'oppressions; thématiques; violences; états-unis

Radical gestures: feminism and performance art in North America - Wark, Jayne (McGill-Queen's University Press, 2006)
Wark brings together a wide range of artists, including Lisa Steele, Martha Rosler, Lynda Benglis, Gillian Collyer, Margaret Dragu, and Sylvie Tourangeau, and provides detailed readings and viewings of individual pieces, many of which have not been studied in detail before. She reassesses assumptions about the generational and thematic characteristics of feminist art, placing feminist performance within the wider context of minimalism, conceptualism, land art, and happenings
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; art contemporain; art féministe; arts; corps; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; militance; performance; premier cycle; périodes historiques; régions géographiques; thématiques

Unveiled Sentiments: Gendered Islamophobia and Experiences of Veiling among Muslim Girls in a Canadian Islamic School - Zine, Jasmin (Equity & Excellence in Education, 2006)
The practice of veiling has made Muslim women subject to dual oppressions--racism and Islamophobia--in society at large and patriarchal oppression and sexism from within their communities. Based on a narrative analysis of the politics of veiling in schools and society, the voices of young Muslim women attending a Canadian Islamic school speak to the contested notion of gender identity in Islam. The narratives situate their various articulations of Islamic womanhood in ways that both affirm and challenge traditional religious notions. At the same time they also are subject to Orientalist representations of veiled and burqa clad women that represent them as oppressed and backward. Focusing on ethnographic accounts of veiling among Muslims girls who attended a gender-segregated Islamic high school in Toronto, this discussion allows a deeper understanding of how gendered religious identities are constructed in the schooling experiences of these Muslim youth. (Contains 11 notes.)
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; corps; cours; discipline; féminisme islamique; intersectionnalité; islamophobie; ontario; patriarcat; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexisme; systèmes d'oppressions; thématiques; toronto; voiles islamiques